Invasive grasses, climate change, and exposure to storm‐wave overtopping in coastal dune ecosystems. (21st December 2012) - Seabloom, Eric W.; Ruggiero, Peter; Hacker, Sally D.; Mull, Jeremy; Zarnetske, Phoebe
Abstract The world's coastal habitats are critical to human well‐being, but are also highly sensitive to human habitat alterations and climate change. In particular, global climate is increasing sea levels and potentially altering storm intensities, which may result in increased risk of flooding in coastal areas. In the Pacific Northwest (USA), coastal dunes that protect the coast from flooding are largely the product of a grass introduced from Europe over a century ago (Ammophila arenaria). An introduced congener (A. breviligulata) is displacing A. arenaria and reducing dune height. Here we quantify the relative exposure to storm‐wave induced dune overtopping posed by the A. breviligulata invasion in the face of projected multi‐decadal changes in sea level and storm intensity. In our models, altered storm intensity was the largest driver of overtopping extent, however the invasion by A. breviligulata tripled the number of areas vulnerable to overtopping and posed a fourfold larger exposure than sea‐level rise over multi‐decadal time scales. Our work demonstrates the importance of a transdisciplinary approach that draws on insights from ecology, geomorphology, and civil engineering to assess the vulnerability of ecosystem services in light of global change.